Anthropogenic impacts on Iberoamerican coastal areas: Historical processes, present challenges, and consequences for coastal zone management - Alveirinho Dias, Joao (2013)
The coastal zone in Portugal, Spain, Brazil and Argentina is declared as a common resource. However, since the touristic boom started in the 1960s, these countries have not considered adequately the available management instruments due to the rapid demand for seaside spaces, the interest to improve rapidly the national economy, and the limitations of the scientific knowledge about the impacts on the natural systems. The environmental consequences of anthropogenically-triggered processes in Latin America occurred somewhat later than in southern Europe, but similar errors were repeated. The investors demanded rapid benefits, without care for social development or environmental protection, and disregarding scientific knowledge. As in other coastal areas of the world, there are strong concerns about the consequences of climate change and sea-level variations on these coasts, especially in areas of extensive urban development.